Enterococcus faecalis utilizes maltose by connecting two incompatible metabolic routes via a novel maltose-6-P phosphatase (MapP) - Mokhtari, Abdelhamid (2013)
Similar to Bacillus subtilis, Enterococcus faecalis transports and phosphorylates maltose via a phosphoenolpyruvate (PEP):maltose phosphotransferase system (PTS). The maltose-specific PTS permease is encoded by the malT gene. However, E. faecalis lacks a malA gene encoding a 6-phospho-a-glucosidase, which in B. subtilis hydrolyses maltose 6-P into glucose and glucose 6-P. Instead, an operon encoding a maltose phosphorylase (MalP), a phosphoglucomutase and a mutarotase starts upstream from malT. MalP was suggested to split maltose 6-P into glucose 1-P and glucose 6-P. However, purified MalP phosphorolyses maltose but not maltose 6-P. We discovered that the gene downstream from malT encodes a novel enzyme (MapP) that dephosphorylates maltose 6-P formed by the PTS. The resulting intracellular maltose is cleaved by MalP into glucose and glucose 1-P. Slow uptake of maltose probably via a maltodextrin ABC transporter allows poor growth for the mapP but not the malP mutant. Synthesis of MapP in a B. subtilis mutant accumulating maltose 6-P restored growth on maltose. MapP catalyses the dephosphorylation of intracellular maltose 6-P, and the resulting maltose is converted by the B. subtilis maltose phosphorylase into glucose and glucose 1-P. MapP therefore connects PTS-mediated maltose uptake to maltose phosphorylase-catalysed metabolism. Dephosphorylation assays with a wide variety of phosphosubstrates revealed that MapP preferably dephosphorylates disaccharides containing an O-aglycosyl linkage